Software-defined instrumentation for microwave network analysis measurement system incorporating virtual calibration technique - Mohd Yassin, Mohd Nazrin (2019)
Network analysis field has existed for decades, but the most commercial analyzers were larger stand-alone benchtop instruments, expensive for individual investment, low volume of production, complex collections of multiple extra components, cables and support instruments. Today, the vector network analyzer (VNA) still considers a huge investment for education, small-medium industries, and researcher lab. In this thesis, we make measurement evolution, delivering promising low-cost VNA measurement system based reconfigurable Software Defined Radio (SDR) platform. The main contribution of this research is the design of a lowcost reconfigurable VNA based on SDR platform using minimal components and utilize open source signal processing framework, GNU Radio software. The traditional method utilizing the GNU Radio relies on its GUI Sink module only were unable to extract baseband complex data immediately. A new methodology to perform data acquisition from the GNU Radio Software is developed in order to establish signal characteristic from SDRs. This work was motivated by the possibility to realize a low cost and fast development cycle time implementation of VNA using SDR integrate with the test set components to define new terminology known as VNA of Software Defined Instrumentation (VNA-SDI). This VNA-SDI platform operates in the 70 MHz to 6 GHz range, and support channel bandwidths from 200 kHz to 56 MHz. The commercial mechanical calibration standard used to validate oneport calibration process applied on VNA-SDI. This proposes a measurement system is to replace the commercial VNA with a low-cost portable unit that can characterize, generate, transmit and receive signals, across a wideband with good repeatability and stability. The performance of the measurement system is verified by showing that the Scattering parameters (S-parameters) of the one-port antenna as devices under test have closed an agreement to results from a commercial VNA within +/-10 dB offset. The second contribution is introduced a method one-port self-calibration or known virtual calibration, which uses impedance emulation block to provided characteristic of OPEN, SHORT, and LOAD during performing calibration. This impedance emulation block was implemented on GNU Radio block to manipulate magnitude factor, phase offset and, phase delay. In consideration of the application, the proposed approach reduces the mechanical complexity of the calibration procedure significantly, by eliminating external calibration. This enables simplified automation of the measurement setup, thus to make VNA-SDI calibration faster, simpler, and easier than traditional mechanical calibration.